A super high temperature resistant nickel-chromium alloy and a manufacturing method thereof

By using multi-layer coating and special heat treatment processes in nickel-chromium alloys to form a microstructure with diffusion distribution of γ' phase, the creep fracture and oxidative peeling problems of traditional nickel-chromium alloys under extreme high temperature conditions are solved, and its high-temperature performance and reliability are significantly improved.

CN119753434APending Publication Date: 2025-04-04JIANGYIN CHENGXIN ALLOY MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411960155.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Traditional nickel-chromium alloys have creep fracture and oxidative peeling problems under extremely high temperature conditions, which limits their service life and reliability, and at the same time, the preparation process is complex and costly.

Method used

Ultra-high temperature resistant nickel-chromium alloy is adopted, which includes a nickel-chromium titanium alloy body, KNM1000 high temperature resistant nanocoating, NiCr-Cr3C2 thermal spray alloy powder coating, nickel-chromium titanium alloy thermal spray sealant coating and ceramic coating, and a fine and uniform microstructure with diffusion distribution of γ' phase is formed through a special heat treatment process.

Benefits of technology

It significantly improves the high-temperature strength and oxidation resistance of the alloy, enhances corrosion resistance, improves processability and welding performance, extends service life, reduces production costs, and is suitable for equipment in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753434A_ABST
    Figure CN119753434A_ABST
Patent Text Reader

Abstract

The invention discloses an ultra-high temperature resistant nickel-chromium alloy and a manufacturing method thereof, and relates to the field of nickel-chromium alloy manufacturing. In actual use, the synergistic effect of chromium (Cr), cobalt (Co), molybdenum (Mo) and tungsten (W) elements significantly improves the high temperature strength and oxidation resistance of the alloy; aluminum (Al) and titanium (Ti) elements help to form a stable oxide film, further enhancing the corrosion resistance; trace amounts of boron (B) and carbon (C) improve the machinability and welding performance of the alloy, and the alloy is suitable for equipment working in high temperature environments such as aerospace engines and gas turbines, and has excellent high temperature strength, oxidation resistance and corrosion resistance, and solves the problems that the alloy still has shortcomings under extreme conditions (such as temperatures exceeding 1000°C), such as creep fracture and oxidation spalling, which limit its service life and reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nickel-chromium alloy manufacturing, and in particular to an ultra-high temperature resistant nickel-chromium alloy and a manufacturing method thereof. Background Art

[0002] Nickel-chromium alloy, commonly known as stainless steel, is an alloy with high strength and corrosion resistance. With the development of modern industry, higher requirements are placed on the high temperature resistance of materials, especially in equipment working in high temperature environments such as aerospace engines and gas turbines. Although traditional nickel-chromium alloys have certain high temperature strength and oxidation resistance, they still have shortcomings under extreme conditions (such as temperatures exceeding 1000°C), such as creep fracture and oxidation peeling, which limit their service life and reliability. In addition, the preparation process of traditional alloys is complicated and costly, making it difficult to meet the needs of large-scale production. Summary of the invention

[0003] In view of the problems in the related art, the present invention proposes an ultra-high temperature resistant nickel-chromium alloy and a manufacturing method thereof to overcome the above technical problems existing in the existing related art.

[0004] To this end, the specific technical solution adopted by the present invention is as follows:

[0005] A super high temperature resistant nickel-chromium alloy comprises a super high temperature resistant nickel-chromium alloy body, a KNM1000 high temperature resistant nano coating is arranged on the periphery of the super high temperature resistant nickel-chromium alloy body, a NiCr-Cr3C2 thermal spray alloy powder coating is arranged on one side of the KNM1000 high temperature resistant nano coating, a nickel-chromium-titanium alloy thermal spray sealing agent coating is arranged on one side of the NiCr-Cr3C2 thermal spray alloy powder coating, and a ceramic coating is arranged on one side of the nickel-chromium-titanium alloy thermal spray sealing agent coating.

[0006] The super high temperature resistant nickel-chromium alloy body is made of the following raw materials by mass:

[0007] Nickel (Ni) 45-60 parts, chromium (Cr) 20-30 parts, cobalt (Co) 5-10 parts, aluminum (Al) 2-6 parts, titanium (Ti) 1-3 parts, molybdenum (Mo) 1-5 parts, tungsten (W) 1-4 parts, carbon (C) 0.05-0.2 parts, boron (B) 0.01-0.1 parts, silicon (Si) 0.2-1.0 parts.

[0008] Furthermore, the super high temperature resistant nickel-chromium alloy also contains 1-2 parts of rare earth elements.

[0009] Furthermore, the rare earth elements include the following raw materials in parts by mass:

[0010] 0.2-0.4 parts of yttrium, 0.4-0.5 parts of lanthanum, 0.3-0.6 parts of cerium, and 0.3-0.5 parts of neodymium.

[0011] According to another aspect of the present invention, there is also provided a method for manufacturing an ultra-high temperature resistant nickel-chromium alloy, comprising the following steps:

[0012] Step S102: placing the pretreated raw material into a vacuum induction furnace, heating it to 1500-1700°C under the protection of high-purity argon, and maintaining it for a certain period of time after it is completely melted to ensure uniform composition; then rapidly cooling it to room temperature to obtain a cast alloy ingot;

[0013] Step S103: heating the cast alloy ingot to 1100-1200° C. and performing multiple forging deformations to densify the internal structure of the alloy and reduce pores and cracks; after each forging, appropriate intermediate annealing treatment is required to restore the plasticity of the material;

[0014] Step S104: heating the hot-forged alloy to 1150-1250° C. and keeping the temperature for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; then rapidly quenching to room temperature to form a supersaturated solid solution;

[0015] Step S105: keeping the quenched alloy at 800-900°C for 10-20 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; finally, slowly cooling to room temperature to obtain the final microstructure;

[0016] Step S106: performing surface treatment on the finished alloy.

[0017] Furthermore, in step S101, the pretreated raw material is placed in a drying oven and dried at 100-150° C. for 2-4 hours to completely remove moisture.

[0018] Furthermore, in step S102, the pretreated raw materials are placed in a vacuum induction furnace and evacuated to below 10^-3Pa; under the protection of high-purity argon, the temperature is gradually raised to 1500-1700°C, and after all the raw materials are completely melted, the temperature is kept warm for 15-30 minutes to ensure uniform composition; the raw materials are quickly cooled to room temperature, the cast alloy ingot is taken out, the appearance quality is checked, and various parameters of the smelting process are recorded.

[0019] Furthermore, in step S103, the cast alloy ingot is heated to 1100-1200°C and kept warm for 1-2 hours to soften the alloy; multiple forging deformations are performed using a hydraulic press or hammering, and the deformation amount each time is controlled between 20%-40%; after each forging, the alloy is immediately placed in a resistance furnace and kept warm at 900-1000°C for 1-2 hours for intermediate annealing to restore the plasticity of the material; the above steps are repeated until the desired size and shape are achieved, and the deformation amount and temperature changes during the forging process are recorded.

[0020] Furthermore, in step S104, the hot forged alloy is heated to 1150-1250°C and kept warm for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; the alloy is quickly transferred to water or oil for quenching, and the cooling rate is controlled at 100-200°C / s to form a supersaturated solid solution; the hardness and metallographic structure of the alloy after quenching are checked, and the temperature and time parameters during the solution treatment process are recorded.

[0021] Furthermore, in step S105, the quenched alloy is placed in a resistance furnace and kept at 800-900°C for 10-20 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; slowly cooled to room temperature to avoid generating large thermal stress; the mechanical properties of the alloy after aging treatment, such as hardness, tensile strength, and yield strength, are checked, and the temperature and time parameters during the aging treatment are recorded.

[0022] Furthermore, in step S106, the finished alloy is subjected to surface treatments such as polishing, sandblasting, electroplating, and coating with a protective coating, the performance indicators of the treated alloy are tested, and the process parameters during the surface treatment process are recorded to obtain a finished ultra-high temperature resistant nickel-chromium alloy.

[0023] Wherein, the raw material components adopted in the present invention are described as follows:

[0024] Nickel (Ni): Atomic number 28, atomic weight 58.6934, located in the fourth period, group VIII, is a hard, ductile, ferromagnetic, silvery-white transition metal. Nickel has good thermal and electrical conductivity, strong plasticity, high temperature resistance, corrosion resistance, chemical stability, and strong antioxidant properties.

[0025] Chromium (Cr): Atomic number is 24, belonging to Group VIB in the periodic table. The element name comes from Greek, which means "color" because chromium compounds have colors. The element is a steel-gray metal and is the hardest metal in nature.

[0026] Cobalt (Co): Ranked 27th in the periodic table, it is a metal element with a hard and brittle texture. Its melting point is about 1500℃, boiling point is about 3100℃, relative density is 8.9g / cm3, and Mohs hardness is 5-5.5. Cobalt has many characteristics. It can maintain high strength at high temperatures, has low thermal conductivity and electrical conductivity, and strong ferromagnetism.

[0027] Aluminum (Al): Atomic number is 13. Its single substance is a silvery-white light metal. It is ductile. Commodities are often made into rods, sheets, foils, powders, strips and filaments. In humid air, it can form an oxide film to prevent metal corrosion. Aluminum powder can burn violently when heated in air, and emits a dazzling white flame. It is easily soluble in dilute sulfuric acid, nitric acid, hydrochloric acid, sodium hydroxide and potassium hydroxide solutions, and difficult to dissolve in water. Relative density 2.70. Melting point 660℃. Boiling point 2327℃. The content of aluminum in the earth's crust is second only to oxygen and silicon, ranking third, and it is the most abundant metal element in the earth's crust. The development of the three major industries of aviation, construction, and automobiles requires that the material properties have the unique properties of aluminum and its alloys, which greatly facilitates the production and application of metal aluminum. It is widely used.

[0028] Titanium (Ti): A transition metal element in the fourth group of the fourth period of the periodic table (titanium subgroup), element symbol Ti, atomic number 22, relative atomic mass 47.867. Titanium is a hard, shiny, silvery white metal with hexagonal α phase and cubic β phase. Relative density is 4.506, melting point is 1668℃, boiling point is 3287℃. Resistivity is 42x10 -8 Ω·m (20℃). In nature, it mainly exists in the form of rutile, perovskite, ilmenite, etc. Titanium sponge is obtained by reducing titanium tetrachloride with magnesium at high temperature, and then melting it by electric arc method to obtain titanium ingot.

[0029] Molybdenum (Mo): Pure molybdenum is a dark grey or black powder or a silvery white mass with a metallic luster. It does not occur naturally in pure metallic form. It occurs mainly as oxides or sulfides. Therefore, almost all exposures are molybdenum compounds rather than the actual metal alone. Important naturally occurring molybdenum compounds are the minerals molybdenite, wolframite, ferromolybdenite, and ferromanganese. Molybdenum has a very high melting point and is widely used in industry to make steel alloys.

[0030] Tungsten (W): Tungsten is a metal element with the symbol W and the atomic number 74. It is in the VIB group of the sixth period of the periodic table. Tungsten is mainly a hexavalent cation in nature, and its ion radius is 0.68×10-10m. Since W6+ has a small ion radius, high charge, strong polarization ability, and is easy to form complex anions, tungsten is mainly in the form of complex anions (WO4)2-, which combines with cations such as Fe2+, Mn2+, and Ca2+ in the solution to form wolframite or scheelite precipitation.

[0031] Carbon (C): Carbon is a non-metallic element with the chemical symbol C. It is stable at room temperature, not easy to react, and has extremely low toxicity to the human body. It can even be safely ingested in the form of graphite or activated carbon. It is located in the second period of the periodic table, IVA group. Carbon is a very common element, which is widely present in the atmosphere, the earth's crust, and living things in various forms.

[0032] Boron (B): It is the first element of the IIIA group of the periodic system, with an atomic structure of 1s22s22p1 and an atomic weight of 10.81. Natural boron is composed of two stable isotopes, and the content of boron in the earth's crust is 0.001%. Boron is a black or brown powder. Crystalline boron is black in appearance, and its hardness is second only to diamond, and its texture is relatively brittle.

[0033] Silicon (Si): A non-metallic element in the 14th group of the third period of the periodic table, with the element symbol Si, the atomic number 14, and the relative atomic mass 28.086. There are two types of single substances: crystalline and amorphous. Crystalline silicon is blue-gray, with a relative density of 2.32-2.34 g / cm3, a melting point of 1414°C, and a boiling point of 2355°C. Amorphous silicon is a gray-black powder, insoluble in water and hydrogen fluoride solution, but soluble in alkali and a mixture of hydrogen fluoride and nitric acid. Crystalline silicon has obvious conductivity, which is less than that of metal, and increases with increasing temperature. High-purity silicon doped with trace phosphorus can be used to prepare n-type semiconductors, and doped with trace boron can be used to prepare p-type semiconductors. It is inactive at room temperature and has no obvious effect on air, water, and acid (except hydrofluoric acid and its mixed acid). It can slowly dissolve in concentrated alkaline solution to form soluble silicates and release hydrogen. It can react with halogens to form silicon tetrahalide when heated. At high temperatures, it can react with non-metallic elements such as oxygen, carbon, nitrogen, and sulfur. It can also react with metals such as calcium and magnesium to form corresponding metal silicides. It can be dissolved in a mixed acid of concentrated nitric acid and hydrofluoric acid to form silicon dioxide, which then dissolves into silicon tetrafluoride.

[0034] Yttrium: Yttrium is a soft, shiny, silvery-white metal that belongs to Group 3 in the periodic table and is the first d-block element in the fifth period. Pure yttrium in bulk forms a protective oxide layer (Y2O3) on the surface in the air. This "passivation" process makes it relatively stable. When heated to 750°C in water vapor, the thickness of the protective layer can reach 10 microns. However, yttrium powder is very unstable in air, and its metal chips can burn in air above 400°C. Yttrium metal will form yttrium nitride (YN) when heated to 1000°C in nitrogen.

[0035] Lanthanum: atomic number 57, relative atomic mass 138.9055. A relatively soft silvery white metal with hexagonal a phase and cubic β phase. Relative density is 6.145 (a), 6.17 (β), melting point 921°C, boiling point 3464°C. Resistivity 57x10-8Ω·m (25°C). Lanthanum is an active metal that loses its luster in the air and forms white lanthanum oxide on the surface. It can burn when heated in the air to form oxides and nitrides; it can form hydrides when heated in hydrogen; it reacts with water to release hydrogen and is easily soluble in acid. The main oxidation state is +3. Important compounds include lanthanum oxide, lanthanum hydroxide, lanthanum oxysulfide, lanthanum oxyhalide and lanthanum halide.

[0036] Cerium: Atomic number 58, belonging to rare earth elements, also belongs to the lanthanide elements of the sixth period system, element symbol Ce, single substance is silver-gray active metal, powder is easy to spontaneously combust in the air, easily soluble in acid and reducing agent. The name of cerium comes from the English name of Ceres. The content of cerium in the earth's crust is about 0.0046%, which is the most abundant among rare earth elements.

[0037] Neodymium: Atomic number 60, one of the lanthanide elements, silvery white metal in its pure form, one of the most active rare earth metals, melting point 1024°C, density 7.004g / cm3, paramagnetic. It can quickly darken in the air and generate oxides; it reacts slowly in cold water and quickly in hot water. Neodymium-doped yttrium aluminum garnet and neodymium glass can replace ruby ​​as laser materials, and neodymium and praseodymium glass can be used to make goggles. Neodymium plays an important role in the field of rare earths.

[0038] The beneficial effects of the present invention are:

[0039] (1) In actual use, the synergistic effect of chromium (Cr), cobalt (Co), molybdenum (Mo) and tungsten (W) elements significantly improves the high temperature strength and oxidation resistance of the alloy; aluminum (Al) and titanium (Ti) elements help to form a stable oxide film, further enhancing the corrosion resistance; trace amounts of boron (B) and carbon (C) improve the machinability and welding performance of the alloy, making it suitable for equipment working in high temperature environments such as aerospace engines and gas turbines, with excellent high temperature strength, oxidation resistance and corrosion resistance, solving the problems of still having deficiencies under extreme conditions (such as temperatures exceeding 1000°C), such as creep rupture and oxidation spalling, which limit its service life and reliability.

[0040] (2) In actual use of the present invention, after a special heat treatment process, the alloy presents a microstructure in which a fine and uniform γ' phase is dispersed in the matrix, and the average grain size is less than 5 μm. This microstructure not only gives the alloy excellent high-temperature strength and ductility, but also effectively inhibits grain boundary sliding and creep phenomena at high temperatures, and also solves the problem that the preparation process of traditional alloys is complicated and costly, making it difficult to meet the needs of large-scale production.

[0041] (3) In actual use of the present invention, when yttrium, lanthanum, cerium and neodymium are added to the alloy, yttrium can form fine and evenly distributed yttrium oxide particles. These particles act as obstacles to dislocation movement and can effectively enhance the alloy's creep resistance at high temperatures. Lanthanum and cerium can react with impurities in the alloy to form fine and evenly distributed second phase particles. These particles can hinder dislocation movement and enhance the alloy's strength and creep resistance at high temperatures. Neodymium can increase the hardness of the alloy surface, thereby improving wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 This is one of the flow charts of a method for manufacturing an ultra-high temperature resistant nickel-chromium alloy according to an embodiment of the present invention;

[0044] Figure 2 This is a second flow chart of a method for manufacturing an ultra-high temperature resistant nickel-chromium alloy according to an embodiment of the present invention;

[0045] Figure 3 It is a schematic diagram of the main structure of an ultra-high temperature resistant nickel-chromium alloy according to an embodiment of the present invention. DETAILED DESCRIPTION

[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] According to the super high temperature resistant nickel-chromium alloy of the embodiment of the present invention, Figure 1-3 As shown, it includes an ultra-high temperature resistant nickel-chromium alloy body 1, a KNM1000 high temperature resistant nano coating 2 is provided on the periphery of the ultra-high temperature resistant nickel-chromium alloy body 1, a NiCr-Cr3C2 thermal spray alloy powder coating 3 is provided on one side of the KNM1000 high temperature resistant nano coating 2, a nickel-chromium-titanium alloy thermal spray sealing agent coating 4 is provided on one side of the NiCr-Cr3C2 thermal spray alloy powder coating 3, and a ceramic coating 5 is provided on one side of the nickel-chromium-titanium alloy thermal spray sealing agent coating 4.

[0048] KNM1000 high temperature resistant nano coating 2 is composed of aluminum oxide, nano manganese dioxide, nano molybdenum oxide and other components, which can form a dense inorganic ceramic coating during high temperature treatment to prevent the oxidation and diffusion of the substrate surface elements to the outside world. It has excellent properties such as high temperature resistance, wear resistance and corrosion resistance, and is suitable for nickel-chromium stainless steel surfaces. NiCr-Cr3C2 thermal spray alloy powder coating 3 has the characteristics of corrosion resistance and high temperature resistance, and is suitable for protection in high temperature environments. Its components include nickel and chromium carbide, and have good adhesion and durability. Nickel-chromium-titanium alloy thermal spray sealing agent coating (4) uses inorganic-organic silicone resin as a film-forming material, and adds nano graphite flakes, nano alumina powder and other materials. It has high temperature resistance (up to 1200°C), good adhesion, wear resistance and impact strength, and is suitable for preventing high temperature oxidation and corrosion. Ceramic coating (5) Ceramic coating can significantly improve the hardness of the nickel-chromium-titanium alloy surface, enhance its scratch resistance and wear resistance, thereby extending the service life of the material.

[0049] The super high temperature resistant nickel-chromium alloy body 1 is made of the following raw materials in parts by weight:

[0050] Nickel (Ni) 45-60 parts, chromium (Cr) 20-30 parts, cobalt (Co) 5-10 parts, aluminum (Al) 2-6 parts, titanium (Ti) 1-3 parts, molybdenum (Mo) 1-5 parts, tungsten (W) 1-4 parts, carbon (C) 0.05-0.2 parts, boron (B) 0.01-0.1 parts, silicon (Si) 0.2-1.0 parts.

[0051] Super high temperature resistant nickel-chromium alloy also contains 1-2 parts of rare earth elements.

[0052] Rare earth elements include the following raw materials by mass:

[0053] 0.2-0.4 parts of yttrium, 0.4-0.5 parts of lanthanum, 0.3-0.6 parts of cerium, and 0.3-0.5 parts of neodymium.

[0054] According to another aspect of the present invention, a method for manufacturing an ultra-high temperature resistant nickel-chromium alloy is also provided. Figure 1-2 As shown, the following steps are included:

[0055] Step S102: placing the pretreated raw material into a vacuum induction furnace, heating it to 1500-1700°C under the protection of high-purity argon, and maintaining it for a certain period of time after it is completely melted to ensure uniform composition; then rapidly cooling it to room temperature to obtain a cast alloy ingot;

[0056] Step S103: heating the cast alloy ingot to 1100-1200° C. and performing multiple forging deformations to densify the internal structure of the alloy and reduce pores and cracks; after each forging, appropriate intermediate annealing treatment is required to restore the plasticity of the material;

[0057] Step S104: heating the hot-forged alloy to 1150-1250° C. and keeping the temperature for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; then rapidly quenching to room temperature to form a supersaturated solid solution;

[0058] Step S105: keeping the quenched alloy at 800-900°C for 10-20 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; finally, slowly cooling to room temperature to obtain the final microstructure;

[0059] Step S106: performing surface treatment on the finished alloy.

[0060] In step S101, the pretreated raw material is placed in a drying oven and dried at 100-150° C. for 2-4 hours to completely remove moisture.

[0061] In step S102, the pretreated raw materials are placed in a vacuum induction furnace and evacuated to below 10^-3Pa; under the protection of high-purity argon, the temperature is gradually raised to 1500-1700°C, and after all the raw materials are completely melted, the temperature is kept for 15-30 minutes to ensure uniform composition; the raw materials are quickly cooled to room temperature, the cast alloy ingot is taken out, the appearance quality is checked, and various parameters during the smelting process are recorded.

[0062] In step S103, the cast alloy ingot is heated to 1100-1200°C and kept warm for 1-2 hours to soften the alloy; multiple forging deformations are performed using a hydraulic press or hammering, and the deformation amount each time is controlled between 20% and 40%; after each forging, the alloy is immediately placed in a resistance furnace and kept warm at 900-1000°C for 1-2 hours for intermediate annealing to restore the plasticity of the material; the above steps are repeated until the desired size and shape are achieved, and the deformation amount and temperature changes during the forging process are recorded.

[0063] In step S104, the hot forged alloy is heated to 1150-1250°C and kept warm for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; the alloy is quickly transferred to water or oil for quenching, and the cooling rate is controlled at 100-200°C / s to form a supersaturated solid solution; the hardness and metallographic structure of the alloy after quenching are checked, and the temperature and time parameters during the solution treatment process are recorded.

[0064] In step S105, the quenched alloy is placed in a resistance furnace and kept at 800-900°C for 10-20 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; slowly cooled to room temperature to avoid generating large thermal stress; the mechanical properties of the alloy after aging treatment, such as hardness, tensile strength, and yield strength, are checked, and the temperature and time parameters during the aging treatment are recorded.

[0065] In step S106, the finished alloy is subjected to surface treatments such as polishing, sandblasting, electroplating, and coating with a protective coating, the performance indicators of the treated alloy are tested, and the process parameters during the surface treatment process are recorded to obtain a finished ultra-high temperature resistant nickel-chromium alloy.

[0066] Embodiment 1:

[0067] The ultra-high temperature resistant nickel-chromium alloy according to an embodiment of the present invention is made of the following raw materials in parts by weight:

[0068] 45 parts of nickel (Ni), 20 parts of chromium (Cr), 5 parts of cobalt (Co), 2 parts of aluminum (Al), 1 part of titanium (Ti), 1 part of molybdenum (Mo), 1 part of tungsten (W), 0.05 parts of carbon (C), 0.01 parts of boron (B), and 0.2 parts of silicon (Si).

[0069] Super high temperature resistant nickel-chromium alloy also contains 1 part of rare earth elements.

[0070] Rare earth elements include the following raw materials by mass:

[0071] 0.2 parts of yttrium, 0.4 parts of lanthanum, 0.3 parts of cerium, and 0.3 parts of neodymium.

[0072] The method for manufacturing the ultra-high temperature resistant nickel-chromium alloy comprises the following steps:

[0073] Step S102: placing the pretreated raw material into a vacuum induction furnace, heating it to 1500° C. under the protection of high-purity argon gas, and maintaining it for a certain period of time after it is completely melted to ensure uniform composition; then rapidly cooling it to room temperature to obtain a cast alloy ingot;

[0074] Step S103: heating the as-cast alloy ingot to 1100° C. and performing multiple forging deformations to densify the internal structure of the alloy and reduce pores and cracks; after each forging, appropriate intermediate annealing treatment is required to restore the plasticity of the material;

[0075] Step S104: heating the hot-forged alloy to 1150° C. and keeping the temperature for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; then rapidly quenching to room temperature to form a supersaturated solid solution;

[0076] Step S105: keeping the quenched alloy at 800°C for 10-20 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; finally, slowly cooling to room temperature to obtain the final microstructure;

[0077] Step S106: performing surface treatment on the finished alloy.

[0078] In step S101, the pretreated raw material is placed in a drying oven and dried at 100-150° C. for 2-4 hours to completely remove moisture.

[0079] In step S102, the pretreated raw materials are placed in a vacuum induction furnace and evacuated to below 10^-3Pa; under the protection of high-purity argon, the temperature is gradually raised to 1500°C, and after all the raw materials are completely melted, the temperature is kept for 15 minutes to ensure uniform composition; the raw materials are quickly cooled to room temperature, the cast alloy ingot is taken out, the appearance quality is checked, and various parameters of the smelting process are recorded.

[0080] In step S103, the cast alloy ingot is heated to 1100°C and kept warm for 1 hour to soften the alloy; multiple forging deformations are performed using a hydraulic press or hammering, and the deformation amount is controlled to be 20% each time; after each forging, the alloy is immediately placed in a resistance furnace and kept warm at 900°C for 1 hour for intermediate annealing to restore the plasticity of the material; the above steps are repeated until the desired size and shape are achieved, and the deformation amount and temperature changes during the forging process are recorded.

[0081] In step S104, the hot forged alloy is heated to 1150°C and kept warm for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; the alloy is quickly transferred to water or oil for quenching, and the cooling rate is controlled at 100°C / s to form a supersaturated solid solution; the hardness and metallographic structure of the alloy after quenching are checked, and the temperature and time parameters during the solution treatment process are recorded.

[0082] In step S105, the quenched alloy is placed in a resistance furnace and kept at 800°C for 10 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; it is slowly cooled to room temperature to avoid generating large thermal stress; the mechanical properties of the alloy after aging treatment, such as hardness, tensile strength, and yield strength, are checked, and the temperature and time parameters during the aging treatment are recorded.

[0083] In step S106, the finished alloy is subjected to surface treatments such as polishing, sandblasting, electroplating, and coating with a protective coating, the performance indicators of the treated alloy are tested, and the process parameters during the surface treatment process are recorded to obtain a finished ultra-high temperature resistant nickel-chromium alloy.

[0084] Embodiment 2

[0085] The ultra-high temperature resistant nickel-chromium alloy according to an embodiment of the present invention is made of the following raw materials in parts by weight:

[0086] 52.5 parts of nickel (Ni), 25 parts of chromium (Cr), 7.5 parts of cobalt (Co), 4 parts of aluminum (Al), 2 parts of titanium (Ti), 3 parts of molybdenum (Mo), 2.5 parts of tungsten (W), 0.125 parts of carbon (C), 0.05 parts of boron (B), and 0.6 parts of silicon (Si).

[0087] Super high temperature resistant nickel-chromium alloy also contains 1-2 parts of rare earth elements.

[0088] Rare earth elements include the following raw materials by mass:

[0089] 3 parts of yttrium, 0.45 parts of lanthanum, 0.45 parts of cerium, and 0.4 parts of neodymium.

[0090] The method for manufacturing the ultra-high temperature resistant nickel-chromium alloy comprises the following steps:

[0091] Step S102: placing the pretreated raw material into a vacuum induction furnace, heating it to 1600° C. under the protection of high-purity argon gas, and maintaining it for a certain period of time after it is completely melted to ensure uniform composition; then rapidly cooling it to room temperature to obtain a cast alloy ingot;

[0092] Step S103: heating the as-cast alloy ingot to 1500° C. and performing multiple forging deformations to densify the internal structure of the alloy and reduce pores and cracks; after each forging, appropriate intermediate annealing treatment is required to restore the plasticity of the material;

[0093] Step S104: heating the hot-forged alloy to 1200° C. and keeping the temperature for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; then rapidly quenching to room temperature to form a supersaturated solid solution;

[0094] Step S105: keeping the quenched alloy at 850° C. for 15 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; finally, slowly cooling to room temperature to obtain the final microstructure;

[0095] Step S106: performing surface treatment on the finished alloy.

[0096] In step S101, the pretreated raw material is placed in a drying oven and dried at 125° C. for 3 hours to completely remove moisture.

[0097] In step S102, the pretreated raw materials are placed in a vacuum induction furnace and evacuated to below 10^-3Pa; under the protection of high-purity argon, the temperature is gradually raised to 1600°C, and after all the raw materials are completely melted, the temperature is kept warm for 22.7 minutes to ensure uniform composition; the raw materials are quickly cooled to room temperature, the cast alloy ingot is taken out, the appearance quality is checked, and various parameters of the smelting process are recorded.

[0098] In step S103, the cast alloy ingot is heated to 1150°C and kept warm for 1-2 hours to soften the alloy; multiple forging deformations are performed using a hydraulic press or hammering, and the deformation amount is controlled to be 30% each time; after each forging, the alloy is immediately placed in a resistance furnace and kept warm at 950°C for 1.5 hours for intermediate annealing to restore the plasticity of the material; the above steps are repeated until the desired size and shape are achieved, and the deformation amount and temperature changes during the forging process are recorded.

[0099] In step S104, the hot forged alloy is heated to 1200°C and kept warm for 2 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; the alloy is quickly transferred to water or oil for quenching, and the cooling rate is controlled at 150°C / s to form a supersaturated solid solution; the hardness and metallographic structure of the alloy after quenching are checked, and the temperature and time parameters during the solution treatment process are recorded.

[0100] In step S105, the quenched alloy is placed in a resistance furnace and kept at 850°C for 15 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; slowly cooled to room temperature to avoid generating large thermal stress; the mechanical properties of the alloy after aging treatment, such as hardness, tensile strength, and yield strength, are checked, and the temperature and time parameters during the aging treatment are recorded.

[0101] In step S106, the finished alloy is subjected to surface treatments such as polishing, sandblasting, electroplating, and coating with a protective coating, the performance indicators of the treated alloy are tested, and the process parameters during the surface treatment process are recorded to obtain a finished ultra-high temperature resistant nickel-chromium alloy.

[0102] Embodiment 3

[0103] 60 parts of nickel (Ni), 30 parts of chromium (Cr), 10 parts of cobalt (Co), 6 parts of aluminum (Al), 3 parts of titanium (Ti), 5 parts of molybdenum (M), 4 parts of tungsten (W), 0.2 parts of carbon (C), 0.1 parts of boron (B), and 1.0 parts of silicon (Si).

[0104] Super high temperature resistant nickel-chromium alloy also contains 2 parts of rare earth elements.

[0105] Rare earth elements include the following raw materials by mass:

[0106] 0.4 parts of yttrium, 0.5 parts of lanthanum, 0.6 parts of cerium, and 0.5 parts of neodymium.

[0107] The method for manufacturing the ultra-high temperature resistant nickel-chromium alloy comprises the following steps:

[0108] Step S102: placing the pretreated raw material into a vacuum induction furnace, heating it to 1700° C. under the protection of high-purity argon gas, and maintaining it for a certain period of time after it is completely melted to ensure uniform composition; then rapidly cooling it to room temperature to obtain a cast alloy ingot;

[0109] Step S103: heating the as-cast alloy ingot to 1200° C. and performing multiple forging deformations to densify the internal structure of the alloy and reduce pores and cracks; after each forging, appropriate intermediate annealing treatment is required to restore the plasticity of the material;

[0110] Step S104: heating the hot-forged alloy to 1250° C. and keeping the temperature for 3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; then rapidly quenching to room temperature to form a supersaturated solid solution;

[0111] Step S105: keeping the quenched alloy at 900° C. for 10-20 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; finally, slowly cooling to room temperature to obtain the final microstructure;

[0112] Step S106: performing surface treatment on the finished alloy.

[0113] In step S101, the pretreated raw material is placed in a drying oven and dried at 150° C. for 4 hours to completely remove moisture.

[0114] In step S102, the pretreated raw materials are placed in a vacuum induction furnace and evacuated to below 10^-3Pa; under the protection of high-purity argon, the temperature is gradually raised to 1700°C, and after all the raw materials are completely melted, the temperature is kept for 30 minutes to ensure uniform composition; the raw materials are quickly cooled to room temperature, the cast alloy ingot is taken out, the appearance quality is checked, and various parameters during the smelting process are recorded.

[0115] In step S103, the cast alloy ingot is heated to 1200°C and kept warm for 1-2 hours to soften the alloy; multiple forging deformations are performed using a hydraulic press or hammering, and the deformation amount each time is controlled between 40%; after each forging, the alloy is immediately placed in a resistance furnace and kept warm at 1000°C for 1-2 hours for intermediate annealing to restore the plasticity of the material; the above steps are repeated until the desired size and shape are achieved, and the deformation amount and temperature changes during the forging process are recorded.

[0116] In step S104, the hot forged alloy is heated to 1250°C and kept warm for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; the alloy is quickly transferred to water or oil for quenching, and the cooling rate is controlled at 200°C / s to form a supersaturated solid solution; the hardness and metallographic structure of the alloy after quenching are checked, and the temperature and time parameters during the solution treatment process are recorded.

[0117] In step S105, the quenched alloy is placed in a resistance furnace and kept at 900°C for 20 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; it is slowly cooled to room temperature to avoid generating large thermal stress; the mechanical properties of the alloy after aging treatment, such as hardness, tensile strength, and yield strength, are checked, and the temperature and time parameters during the aging treatment are recorded.

[0118] In step S106, the finished alloy is subjected to surface treatments such as polishing, sandblasting, electroplating, and coating with a protective coating, the performance indicators of the treated alloy are tested, and the process parameters during the surface treatment process are recorded to obtain a finished ultra-high temperature resistant nickel-chromium alloy.

[0119] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An ultra-high temperature resistant nickel-chromium alloy, characterized in that: The invention comprises an ultra-high temperature resistant nickel-chromium alloy body (1), wherein a KNM1000 high temperature resistant nano coating (2) is disposed on the periphery of the ultra-high temperature resistant nickel-chromium alloy body (1), a NiCr-Cr3C2 thermal spray alloy powder coating (3) is disposed on one side of the KNM1000 high temperature resistant nano coating (2), a nickel-chromium-titanium alloy thermal spray sealing agent coating (4) is disposed on one side of the NiCr-Cr3C2 thermal spray alloy powder coating (3), and a ceramic coating (5) is disposed on one side of the nickel-chromium-titanium alloy thermal spray sealing agent coating (4).

2. The ultra-high temperature resistant nickel-chromium alloy according to claim 1, characterized in that: The super high temperature resistant nickel-chromium alloy body (1) is made of the following raw materials in parts by weight: Nickel (Ni) 45-60 parts, chromium (Cr) 20-30 parts, cobalt (Co) 5-10 parts, aluminum (Al) 2-6 parts, titanium (Ti) 1-3 parts, molybdenum (Mo) 1-5 parts, tungsten (W) 1-4 parts, carbon (C) 0.05-0.2 parts, boron (B) 0.01-0.1 parts, silicon (Si) 0.2-1.0 parts.

3. The ultra-high temperature resistant nickel-chromium alloy according to claim 2, characterized in that: The ultra-high temperature resistant nickel-chromium alloy also contains 1-2 parts of rare earth elements, and the rare earth elements include the following raw materials in parts by mass: 0.2-0.4 parts of yttrium, 0.4-0.5 parts of lanthanum, 0.3-0.6 parts of cerium, and 0.3-0.5 parts of neodymium.

4. A method for manufacturing an ultra-high temperature resistant nickel-chromium alloy, based on the application of an ultra-high temperature resistant nickel-chromium alloy according to claim 3, characterized in that: The following steps are involved: Step S101: weighing the raw materials required for the ultra-high temperature resistant nickel-chromium alloy according to the above mass fractions, and pre-treating them to remove surface oxides and other impurities; Step S102: placing the pretreated raw material into a vacuum induction furnace, heating it to 1500-1700°C under the protection of high-purity argon, and maintaining it for a certain period of time after it is completely melted to ensure uniform composition; then rapidly cooling it to room temperature to obtain a cast alloy ingot; Step S103: heating the cast alloy ingot to 1100-1200° C. and performing multiple forging deformations to densify the internal structure of the alloy and reduce pores and cracks; after each forging, appropriate intermediate annealing treatment is required to restore the plasticity of the material; Step S104: heating the hot-forged alloy to 1150-1250° C. and keeping the temperature for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; then rapidly quenching to room temperature to form a supersaturated solid solution; Step S105: keeping the quenched alloy at 800-900°C for 10-20 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; finally, slowly cooling to room temperature to obtain the final microstructure; Step S106: performing surface treatment on the finished alloy.

5. The ultra-high temperature resistant nickel-chromium alloy and the method for manufacturing the same according to claim 4, characterized in that: In step S101, the pretreated raw material is placed in a drying oven and dried at 100-150° C. for 2-4 hours to completely remove moisture.

6. The ultra-high temperature resistant nickel-chromium alloy and the method for manufacturing the same according to claim 4, characterized in that: In the step S102, the pretreated raw materials are placed in a vacuum induction furnace and evacuated to below 10^-3Pa; under the protection of high-purity argon, the temperature is gradually raised to 1500-1700°C, and after all the raw materials are completely melted, the temperature is continued to be kept for 15-30 minutes to ensure uniform composition; the raw materials are quickly cooled to room temperature, the cast alloy ingot is taken out, the appearance quality is checked, and various parameters during the smelting process are recorded.

7. The ultra-high temperature resistant nickel-chromium alloy and the method for manufacturing the same according to claim 4, characterized in that: In the step S103, the cast alloy ingot is heated to 1100-1200°C and kept warm for 1-2 hours to soften the alloy; a hydraulic press or hammering method is used to perform multiple forging deformations, and the deformation amount each time is controlled between 20% and 40%; after each forging, the alloy is immediately placed in a resistance furnace and kept warm at 900-1000°C for 1-2 hours for intermediate annealing to restore the plasticity of the material; the above steps are repeated until the desired size and shape are achieved, and the deformation amount and temperature changes during the forging process are recorded.

8. The ultra-high temperature resistant nickel-chromium alloy and the method for manufacturing the same according to claim 4, characterized in that: In the step S104, the hot forged alloy is heated to 1150-1250°C and kept warm for 1-3 hours to allow the strengthening phase in the alloy to fully dissolve in the matrix; the alloy is quickly transferred to water or oil for quenching, and the cooling rate is controlled at 100-200°C / s to form a supersaturated solid solution; the hardness and metallographic structure of the alloy after quenching are checked, and the temperature and time parameters during the solution treatment are recorded.

9. The ultra-high temperature resistant nickel-chromium alloy and the method for manufacturing the same according to claim 4, characterized in that: In the step S105, the quenched alloy is placed in a resistance furnace and kept at 800-900° C. for 10-20 hours to promote the precipitation of the γ' phase from the solid solution to form a fine dispersed strengthening phase; slowly cooled to room temperature to avoid generating large thermal stress; the mechanical properties of the alloy after aging treatment, such as hardness, tensile strength, and yield strength, are checked, and the temperature and time parameters during the aging treatment are recorded.

10. The super high temperature resistant nickel-chromium alloy and the method for manufacturing the same according to claim 4, characterized in that: In step S106, the finished alloy is subjected to surface treatments such as polishing, sandblasting, electroplating, and coating with a protective coating, the performance indicators of the treated alloy are tested, and the process parameters during the surface treatment process are recorded to obtain a finished ultra-high temperature resistant nickel-chromium alloy.

Citation Information

Cited By

  • High-strength high-temperature-resistant alloy material for gas turbine casing and preparation method thereof

    CN121087399A

  • High-strength high-temperature-resistant alloy material for gas turbine casing and preparation method thereof

    CN121087399B